The development of the speed force in youth: pliometric training (foreign innovations) - Сергієнко, Л. П.; Лишевська, В. М. (Physical Education Theory and Methodology, 2012)
The article generalizes a foreign experience of the development of the speed force in young people which go in for sports. The method of pliometric training is described. The technology of using the pliometric exercises for the development of speed force of arms ad legs is given.